Comparison of atomic scale dynamics for the middle and late transition metal nanocatalysts - Cao, Kecheng; Zoberbier, Thilo; Biskupek, Johannes; Botos, Akos; McSweeney, Robert; Kurtoglu, Abdullah; Stoppiello, Craig T.; Markevich, Alexander V.; Besley, Elena; Chamberlain, Thomas W.; Kaiser, Ute; Khlobystov, Andrei N. (Nature Publishing Group, 2018)
Catalysis of chemical reactions by nanosized clusters of transition metals holds the key to the provision of sustainable energy and materials. However, the atomistic behaviour of nanocatalysts still remains largely unknown due to uncertainties associated with the highly labile metal nanoclusters changing their structure during the reaction. In this study, we reveal and explore reactions of nm-sized clusters of technologically important metals in carbon nano test tubes using time-series imaging by atomically-resolved transmission electron microscopy (TEM), employing the electron beam simultaneously as an imaging tool and stimulus of the reactions. Defect formation in nanotubes and growth of new structures promoted by metal nanoclusters enable the ranking of the different metals both in order of their bonding with carbon and their catalytic activity, showing significant variation across the Periodic Table of Elements. Metal nanoclusters exhibit complex dynamics shedding light on atomistic workings of nanocatalysts, with key features mirroring heterogeneous catalysis.